IMPROVING PPKn LEARNING MOTIVATION THROUGH COOPERATIVE LEARNING TYPE INDEX CARD MATCH STUDENTS CLASS VI - Asmanidar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low motivation to learn of class VI students of SD Negeri 021 Tarai Bangun, Kampar Regency. This study aims to increase the learning motivation of Civics in Class VI students of SD Negeri 021 Tarai Bangun, Kampar Regency using Cooperative Learning Type Index Card Match. The subjects of this study were all Class VI students of SD Negeri 021 Tarai Bangun, Kampar Regency, totaling 32 people. The form of research is classroom action research. The research instruments used were a performance instrument and an observation sheet of teacher activity and student activity. The results showed that in Cycle I the research score reached 132 with high criteria, with an average student motivation for each learning motivation indicator of only 68.8%. While the observations of learning motivation in Cycle II reached a score of 163 with very high criteria, the average student motivation for learning motivation indicators was 84.9%. Thus, it can be concluded that through cooperative learning Index Card Match type, students’ Civics learning motivation can be increased.